The Double Dividend Hypothesis of Environmental Taxes: A Survey - Ronnie Schöb (Fondazione Eni Enrico Mattei (FEEM), 2003)
This survey reviews the recent literature on the double-dividend hypothesis of environmental taxes and discusses some extensions of the standard model such as the distributional consequences and the importance of the non-separability assumption between consumption goods and environmental quality for the optimal design of environmental policies. Turning to a model with imperfect labour markets we then show under which circumstances environmental taxes on polluting inputs in production and on polluting consumption goods can reap a second dividend in the form of an employment dividend and discuss the welfare implications. Finally, we turn to international aspects of environmental taxation. When environmental problems are tied to the use of exhaustible resources, resource-consuming countries can appropriate resource rents at the cost of resource-owning countries by levying environmental taxes strategically.
Keywords: H21; H23; J50; Q30; 330; Environmental taxation; Double-dividend hypothesis; Full-employment models; Unemployment models; International coordination; Ökosteuer; Steuerwirkung; Beschäftigungseffekt; Wohlfahrtsanalyse; Internationaler Wettbewerb; Theorie; Doppelte Dividende